Clinician Perceptions of Pediatric Growth Chart Use and Electronic Health Records in Kentucky - Soares, N.; Vyas, K.; Perry, B. (Applied Clinical Informatics, 2012)
Background: Growth chart recording is a key component of pediatric care. EHR systems could provide several growth charting functionalities compared to paper methods. To our knowledge, there has been no U.S. study exploring clinicians’ perceptions and practices related to recording of growth parameters as they adapt to electronic methods.Objectives: To explore clinician practices regarding recording growth parameters as they adapt to electronic health records (EHR) and to investigate clinician perceptions of electronic growth charting using EHR.Methods: An online survey of pediatricians and family practitioners in Kentucky inquiring about EHR usage, specifically use of growth charting with EHR, was conducted.Results: Forty-six percent of respondents utilized EHRs, with pediatricians lagging family practitioners, and academic pediatricians lagging non-academicians. There was no consensus on EHR platforms being used. Almost a third of those who used EHR did not utilize electronic growth charting. Clinicians using EHR reported that electronic growth charts would improve clinician satisfaction and clinical efficiency as well as parent satisfaction and parent education. Only 12% of respondents provided copies of growth charts to parents at the end of their visit and discussed growth parameters with parents, with clinicians using EHR more likely to engage in these activities than nonEHR users.Conclusion: Although Kentucky clinicians continue to slowly adopt EHRs, clinician perceptions and practices reflect enduring barriers to widespread use of electronic growth charting in pediatric and family practice. However, our results suggest that electronic growth charting has important benefits for both clinicians and patients, and greater adoption is expected as EHRs become standard across health care systems.Citation: Soares N, Vyas K, Perry B. Clinician perceptions of pediatric growth chart use and electronic health records in Kentucky. Appl Clin Inf 2012; 3: 437–447http://dx.doi.org/10.4338/ACI-2012-06-RA-0023
Keywords: Growth charts; pediatrics; family practice; electronic health record